BEST PRACTICE FOR AUSTRALIA'S ADAPTATION MONITORING AND EVALUATION FRAMEWORK: CASE COMPARISONS IN THE UK, GERMANY, CANADA, AND FINLAND - Anggita Arum Pertiwi; Carrie Yan; Putra, Fajar Surya; Thas Saralah (Journal of Sustainable Development Issues, 2024)
Climate change adaptation has become a policy priority for over 170 countries, yet significant challenges remain in tracking and evaluating the effectiveness of National Adaptation Plans (NAPs) and National Adaptation Strategies (NASs). A robust Monitoring and Evaluation (M&E) framework is crucial for assessing adaptation effectiveness, but the establishment of such systems faces hurdles, including legal complexities, indicator flexibility, and institutional coordination. While international organizations and scholars propose various M&E frameworks, a gap exists in tailoring these frameworks to specific institutional and cultural contexts. Australia’s adaptation M&E framework remains in its early stages, actively seeking input to refine its assessment structure, tracking metrics, and data collection approaches.This study aims to identify key components of effective adaptation M&E frameworks, analyze best practices from four countries—UK, Germany, Canada, and Finland—that share institutional and cultural similarities with Australia, and synthesize their approaches for potential application in the Australian context. Through a comparative case study methodology, this research identifies six critical components for effective adaptation M&E: (1) theory of change, (2) sectoral-based approach, (3) risk assessment, (4) flexibility and iterative learning, (5) quality of indicators, and (6) accountability mechanisms. Findings indicate that while the UK and Germany have well-established M&E frameworks integrating these components, Canada and Finland are still refining their approaches. Based on these insights, this study provides a best-practice roadmap that can guide Australia in developing a structured, flexible, and comprehensive adaptation M&E framework, ensuring its effectiveness in tracking progress and fostering resilience to climate change.